Relatório de Estágio Curricular no Tribunal Judicial da Comarca dos Açores Secção de Família e Menores de Ponta Delgada, Ilha de São Miguel - Freire, Andreia Sofia Raposo (2020)
The present report was made based on the four months period I have spent in Ponta Delgada’s Family Court. Bearing in mind the particularities of this court, I felt right a way interested in the work that was going on “behind the curtains” of all the reports that almost every day reached the magistrate's hand for his knowledge and that had a fundamental role in his decision. It became obvious, from the beginning, that in this court, in addition to working with laws, we worked with people's lives, and with all the implications that this entails. Thus, it is intended, in addition to providing knowledge of the activities carried out during the internship, to provide a normative and concrete framework of the functions, activities and work of the Advisory Technicians of the Court’s Support Multidisciplinary Team